Utilization of modern menstrual methods and related unmet needs among college going women in Coimbatore district: a descriptive cross-sectional study - Thavansree Durairaj; Periasamy Aparnavi; Seetharaman Narayanan; Sushmitha Mahantshetti; Srihari Dhandapani; Jeevithan Shanmugam; Ramesh Rathinamoorthy; Mohan Kumar (BMC, 2024)
Abstract Objectives The primary objectives were to determine the proportion of modern menstrual method (MMM) users among college going women in Coimbatore district, Tamil Nadu; and to estimate the unmet needs associated with use of MMMs in comparison with other menstrual hygiene methods (MHMs). We also assessed the factors that determine MMM use among college going women. Methods This was a descriptive cross-sectional study conducted among college going women in Coimbatore district, Tamil Nadu, India between October 2022 and January 2023 using a purpose predesigned, pretested, semi-structured proforma that included validated Menstrual Practice Needs Scale (MPNS-36). Results Only 1.4% of the study participants used MMMs - menstrual cups (1.3%) and tampons (0.1%). Sanitary pads were the most common MHM of choice (96.3%); of which majority (98.6%) used disposable pads and more than half (50.4%) used non-biodegradable pads. Importantly, one in six (16.5%) were not aware of nature of sanitary pads (biodegradable or nonbiodegradable) used. The unmet needs associated with MMMs (menstrual cups and tampons) were significantly lower than that for other MHMs (including sanitary pads), in particular, the unmet material and home environment needs, unmet material reliability concerns, unmet reuse needs and unmet reuse insecurity. However, we found no significant difference between MMMs, sanitary pads and other MHMs in terms of unmet transport, college environment, change and disposal insecurity needs. The significant predictors of use of MMMs were age (more than 21 years of age), residence (urban), type of stay (off campus including home), socioeconomic status (upper), fathers' and mothers' education (high school and above), and presence of personal income. Discussions with friends (or peers) both before and after menarche regarding menstruation resulted in higher adoption of modern menstrual methods. Conclusion MMMs provided comparative advantage with lesser unmet needs for material reliability and reuse insecurity concerns, particularly in home environment. However, none of the MHMs fulfilled the user expectations for transport and disposal insecurity concerns, particularly outdoors.